全球化学品统一分类和 标签制度(全球统一制度） - United Nations (United Nations, 2020)
(Chinese Language)The Globally Harmonized System of Classification and Labelling of Chemicals (GHS) addresses classification and labelling of chemicals by types of hazards. It provides the basis for worldwide harmonization of rules and regulations on chemicals and aims at enhancing the protection of human health and the environment during their handling, transport and use by ensuring that the information about their physical, health and environmental hazards is available. The eighth revised edition of the GHS includes: • new classification criteria, hazard communication elements, decision logics and guidance for chemicals under pressure; • new provisions for the use of in vitro/ex vivo data and non-test methods to assess skin corrosion and skin irritation; • miscellaneous amendments to clarify the classification criteria for Specific Target Organ Toxicity; • revised and further rationalized precautionary statements and an editorial revision of Sections 2 and 3 of Annex 3; • new examples of precautionary pictograms to convey the precautionary statement “Keep out reach of children”; • a new example in Annex 7 addressing labelling of sets or kits; • guidance on the identification of dust explosion hazards and the need for risk assessment, prevention, mitigation, and hazard communication.